(3GdCMcGe GdfLhejIs ((3eMeO Hf Ydi GdHbGQ s)
(3ChdgG (B:s
(3CeG HYO , aEf GdbOeGA GdYdeGA hVYhG ai GdehGdjO hGdeSGFd cJHkG JUYH Ydi GdeJYdejf HCZeGV GdCdaGX ef bdI HjGfg aCQOJ Cf CVY UaI Yed UfGYI GdehGdjO hGdeSGFd s
(3BNQgG (B:s
(3hde jYbg YGFb YQVi ef GdCSHGH GdaGSOI dWHYI hZjQ GdedGFeI dCfg YfO Pdc JXgQ TQhQ YXjeI hEPG cGf Ydi VO eG PcQfGg cGfJ OdGdJg Ydi NdGa eG PcQ , hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3cJHJ HQSe eMeO Hf Ydi Hf EOQjS Gdcheis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(939 / 5) s
Keywords: (3Gdadcs